Correction to: Circular Economy and Solid Waste Management: Challenges and Opportunities in Brazil (Circular Economy and Sustainability, (2021), 1, 1, (261-282), 10.1007/s43615-021-00031-2) - Mancini, Sandro Donnini [UNESP]; de Medeiros, Gerson Araújo [UNESP]; Paes, Michel Xocaira; de Oliveira, Benone Otávio Souza; Antunes, Maria Lúcia Pereira [UNESP]; de Souza, Ricardo Gabbay [UNESP]; Ferraz, José Lázaro; Bortoleto, Ana Paula; Puppim de Oliveira, José Antonio (Springer Nature, 2021)
The original publication has been corrected. The name of author José Antonio Puppim de Oliveira is now correctly on the article.